STUDENTS’ LISTENING COMPREHENSION: EFFECT OF TEACHING MEDIA AND LEARNING MOTIVATION - Cicih Nuraeni (LPPM Universitas Bina Sarana Informatika, 2014)
The objective of the research is to know the effect of using teaching media and learning motivation towards students’ listening comprehension. The design of the study was experimental study. The population is all students in 4th semester at Academy Secretary and Management Bina Sarana Informatika and the sample who obtained a random sampling technique is 60 students. The class was taught listening comprehension by using Davitech Teacher Media.In collecting data, it was used multiple choices and questionnaire. The analysis data was used ANOVA Two-ways with significance level of 5%. It was found that the mean score of the experimental class with high learning motivation was 83,20 and low learning motivation was 66,73. For the conventional class with high learning motivation, the mean score was 77 and for the low learning motivation was 56,13. Thus, it is clear that the differences of the means gained score were significant. Therefore, it can be concluded that the application of Davitech Teacher Media and learning motivation on students’ listening comprehension was much more effective.